Основні складові соціальної інтеграції осіб з інвалідністю - Мартинюк, Тетяна (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті визначено та проаналізовано основні складові соціальної інтеграції осіб з інвалідністю, що визначають специфіку її реалізації. Автор розкриває особливості понять «інтеграція», «соціальна інтеграція» та «соціальна інтеграція осіб з інвалідністю». Автор наголошує, що соціальна інтеграція осіб з інвалідністю є складним багатоаспектним, багаторівневим та багатокомпонентним процесом.Значущими складовими соціальної інтеграції осіб з інвалідністю визначено наступні: сутнісна, суб’єктна, цільова, предметно-змістова, методологічна, операційна та результативна. The main components of the social integration of people with disabilities are highlighted and analyzed in the article that determine the specifics of its implementation. The author reveals the peculiarities of the concepts of "integration", "social integration" and "social integration of people with disabilities". The author emphasizes that the process of social integration of the personality is bilateral: a person with a disability can not be only an object of integration, but also, necessarily, acts as a subject, an active participant of this process. Significant components of the social integration of people with disabilities are: substantive, subject, target, subject-content, methodological, operational and effective. The author points out the multidimensional, multilevel and multicomponent nature of the process of social integration of people with disabilities. The activity approach is a basis of social integration of such people, which defines the basic characteristics of this process: sociality, expediency, awareness, ensuring its arbitrariness and regulation, subjectivity, subjectivity, objectivity, planning, mediation. Another important complex defining the essence of social integration of people with disabilities is the introduction of a set of measures (socio-economic, psychological and pedagogical, medical, etc.), inclusion in various types of joint activities. The main results of the social integration of young people with disabilities are the promotion of satisfaction of organic needs, activation of the role of the person with disabilities in the implementation of the complex of social needs and strengthening the role of society and promoting the provision of a complex of social needs of people with disabilities.
Keywords: соціальна інтеграція; особа з інвалідністю; соціальна інтеграція осіб з інвалідністю; складові соціальної інтеграції осіб з інвалідністю